2017
DOI: 10.1038/s41598-017-09915-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping White Matter Microstructure in the One Month Human Brain

Abstract: White matter microstructure, essential for efficient and coordinated transmission of neural communications, undergoes pronounced development during the first years of life, while deviations to this neurodevelopmental trajectory likely result in alterations of brain connectivity relevant to behavior. Hence, systematic evaluation of white matter microstructure in the normative brain is critical for a neuroscientific approach to both typical and atypical early behavioral development. However, few studies have exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
80
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 78 publications
12
80
2
Order By: Relevance
“…When examining each morphometric measure in isolation, developmental trajectories with clear anatomical structure were found across the PMA range examined replicating prior work (Batalle et al, 2019;Dean et al, 2017). Typical measure of cortical anatomy, thickness and area, as well as a good measure of relative T1w contrast, myelin content, showed strong increases with age .…”
Section: Discussionsupporting
confidence: 71%
“…When examining each morphometric measure in isolation, developmental trajectories with clear anatomical structure were found across the PMA range examined replicating prior work (Batalle et al, 2019;Dean et al, 2017). Typical measure of cortical anatomy, thickness and area, as well as a good measure of relative T1w contrast, myelin content, showed strong increases with age .…”
Section: Discussionsupporting
confidence: 71%
“…The resulting axial diffusivity 305 age trajectories are in agreement with previous studies [34][35][36]. However, while these numbers 306 pertain to the whole of white matter, regional differences in developmental trajectories of DTI 307 quantities in the neonate brain have been observed [37]. In the infants, a further look into 308 high FA (¿0.5) regions, which reduce to portions of the corpus callosum and the internal 309 capsule, revealed that average optimal d in these regions is comparable to that seen in the adult global WM.…”
supporting
confidence: 86%
“…In the infants, a further look into 308 high FA (¿0.5) regions, which reduce to portions of the corpus callosum and the internal 309 capsule, revealed that average optimal d in these regions is comparable to that seen in the adult global WM. These regions in the infant are thought to be myelinated by one month after 311 birth and to have higher fiber coherence than other white matter areas [37]. The lower FA 312 regions (not shown) in the infant brain, which presumably reflect less or not-yet myelinated 313 axons and or lower fiber coherence, exhibit values of average optimal d that are similar to 314 those of whole WM.…”
mentioning
confidence: 95%
“…In previous works, we showed the relationship between white matter abnormalities detected by cUSs and GA and the effect on both short-and long-term neurodevelopment played by white matter pattern of maturation (Di Rosa et al, 2016;Marseglia et al, 2015). Qualitative white matter abnormalities could result in widespread brain dysmaturation and were previously related to male gender by BRIEF REPORT 7 of 9 neuroimaging studies (Dean III et al, 2017). In conclusion, an easy clinical temporal assessment revealed different genderrelated profiles of achievement of developmental milestones in our moderate and late PT infants that were persistent at the long-term observation.…”
Section: Discussionmentioning
confidence: 92%